Awareness Program of Pesticides Used among Farmers using Difficulty-Usefulness Pyramid (A Suggestion for Health Laws and Policies Regarding the Use of Pesticides) - Ilyas Ibrahim1 , I Ketut Sudiana2 , H. J. Mukono3 , Suhartono4 , Heru Santoso Wahito Nugroho5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pesticides are toxic chemical substances that are used in agriculture to control plant pests. Excessive use of pesticides and uncontrolled can cause negative effects among farmers, such as vomiting, diarrhea, dyspnea, blurred vision, paresthesia, slurred speech, and chest pain. The prevention effort through health education was used to prevent the risk behavior of farmer, however, it still found obstacles. There are many elements need to be improved and it must be selected which element that significant and priority to change risk behavior among farmers. This study had selected the elements based on Difficulty-Usefulness Pyramid (DUP). The sample was 100 respondents who knew about pesticides in Indonesia. Personal protective equipment (PPE), storage of pesticides, procedure for using pesticides, use of pesticide doses, duration and frequency of spraying pesticides, cleaning the equipment, spraying pesticides based on the wind direction, time of pesticide spraying were selected elements in this study. Difficulty and usefulness were indicators to determine the priority of attributes. Attribute scale (1 to 10) was used based on the level of importance in each attribute. Google form questionnaire was used to collect the data. Each element was measured by: (1) difficulty and usefulness; (2) the mean score of difficulty and the mean score of usefulness; (3) range (from mean score of difficulty to mean score of usefulness). Then the range was sorted starting from the smallest and presented in the form of a pyramid. The pyramid showed that the priority elements were use of pesticide doses, procedures for using pesticides, personal protective equipment (PPE), cleaning the equipment, time spraying pesticides, duration and frequency of spraying pesticides, storage of pesticides, spraying pesticide based on the wind direction.